Use of the 95-degree Angled Blade Plate to Treat a Proximal Femur Fracture. (August 2018) - Hartline, Braden E.; Achor, Timothy S.
Abstract : Summary: There are a variety of ways to treat high-energy proximal femur fractures, including intramedullary nails and laterally based plates. Although each have distinct advantages and disadvantages, fracture reduction and avoiding varus alignment are critical. For some fractures, the blade plate is a reliable, straightforward implant to treat these injuries. This article and the accompanying video describe the surgical technique of using a 95-degree angled blade plate to treat an acute high-energy proximal femur fracture. Abstract : Supplemental Digital Content is Available in the Text.